Reply to Effects of Hormone Replacement Therapy on Sarcopenia: Is It Real?. Issue 6 (30th January 2019) - Follis, Shawna; Bea, Jennifer W.; Cauley, Jane A.; Shadyab, Aladdin H.; Cook, Alan; Chen, Zhao
Abstract : This letter comments on the letter byÜnsal et al .